2022
DOI: 10.3390/biomedicines10050980
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mitochondrial Function in Cell Membranes as Indicator of Tissue Vulnerability to Drugs in Humans

Abstract: Drug side effects are one of the main reasons for treatment withdrawal during clinical trials. Reactive oxygen species formation is involved in many of the drug side effects, mainly by interacting with the components of the cellular respiration. Thus, the early detection of these effects in the drug discovery process is a key aspect for the optimization of pharmacological research. To this end, the superoxide formation of a series of drugs and compounds with antidepressant, antipsychotic, anticholinergic, narc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…In terms of molecular mechanisms, it has been demonstrated that chronic inflammation induces the release of proinflammatory cytokines, such as TNF-α and interleukins, which can trigger the production of ROS in cells [ 115 ]. These ROS can have detrimental effects on mitochondrial function by damaging critical components of the mitochondrial machinery, such as electron transport chain proteins, thereby compromising the energy efficiency of mitochondria [ 122 ]. Anti-inflammatory agents, such as COX inhibitors, may counteract these effects by reducing ROS production and preserving the functional integrity of mitochondria, which potentially could mitigate the progression of mitochondrial dysfunction associated with chronic inflammation [ 121 ].…”
Section: Treatment Options For Treatment-resistant Depressionmentioning
confidence: 99%
“…In terms of molecular mechanisms, it has been demonstrated that chronic inflammation induces the release of proinflammatory cytokines, such as TNF-α and interleukins, which can trigger the production of ROS in cells [ 115 ]. These ROS can have detrimental effects on mitochondrial function by damaging critical components of the mitochondrial machinery, such as electron transport chain proteins, thereby compromising the energy efficiency of mitochondria [ 122 ]. Anti-inflammatory agents, such as COX inhibitors, may counteract these effects by reducing ROS production and preserving the functional integrity of mitochondria, which potentially could mitigate the progression of mitochondrial dysfunction associated with chronic inflammation [ 121 ].…”
Section: Treatment Options For Treatment-resistant Depressionmentioning
confidence: 99%